Literature Review: Intervensi Prone Positioning Dalam Pengelolaan Pasien dengan Acute Respiratory Distress Syndrome - Etika Emaliyawati; Titin Sutini; Ermiati Ermiati; Asep Solehudin; Firman Sugiharto; Restuning Widiasih (Universitas Malahayati Lampung, 2024)
ABSTRACT Acute Respiratory Distress Syndrome (ARDS) is one of the causes of most patients being admitted to the Intensive Care Unit (ICU) and has the potential to cause death due to inadequate gas exchange due to fluid in the alveoli. One of the interventions given is prone positioning to increase lung expansion. This study examines the benefits and impact of prone positioning intervention in ARDS patients. This literature review uses the Preferred Reporting Items for Systematic Reviews (PRISMA) guidelines with the keywords